Regulation, Renegotiation and Capital Structure : Theory and Evidence from Latin American Transport Concessions - Moore, Alexander; Straub, Stéphane; Dethier, Jean-Jacques (World Bank, Washington, DC, 2014)
The paper examines the capital structure of regulated infrastructure firms. The authors develop a model showing that leverage, the ratio of liabilities to assets, is lower under high-powered regulation and that firms operating under high-powered regulation make proportionally larger reductions in leverage when the cost of debt increases. They test the predictions of the model using an original panel dataset of 124 transport concessions in Brazil, Chile, Colombia and Peru over 1992-2011, finding broad support for our predictions.